The Effect of active range of motion (ROM ) on increasing muscle strength in stroke patients at UPTD PUSKESMAS pneureumeue district KAWAY XVI WEST ACEH DISTRICT YEAR 2022 - Joko Sutejo (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
A stroke is called a Cerebro-vascular Accident (CVA) which is a permanent nerve disorder due to disruption of blood circulation to the brain, which occurs for about 24 hours or more. This study aims to determine the effect of active range of motion (ROM) on increasing muscle strength in stroke patients at UPTD Peureumeue health Center Aceh Barat this type of research is qualitative with a quasi-experimental design approach. This study uses pre test and post test designtechniques in stroke patients at Pereumeue Health Center, Aceh Barat, aged 30 minority respondents aged 35-44 years 9 respondents (30,0)and the majority 45-54 years 13 respondents (43,3) 55-64 years 8 respondens (27.7) 30 respondents, the majority were male, 20 respondents (66.7) and the minority were female, as many as 10 respondents (33.3). that N or the number of data in this study were 30 respondents, then the significant value (2-tailed) was 0.000 because the sig (2-tailed) value was 0,00<0.05, it means that there is an effect of range of motion on increasing muscle strength in Stroke patient. Based on this research, it is recommended for health workers to provide health education to the public, especially about stroke and how to prevent it. For further researchers, it is expected to recognize the active range ofmotion (ROM) for increasing muscle strength in stroke patients.